Enhanced Food-Production Efficiencies through Integrated Farming Systems in the Hau Giang Province in the Mekong Delta, Vietnam - Håkan Berg; Nguyen Thanh Tam; Thai Huynh Phuong Lan; Chau Thi Da (Agriculture, 2024)
This study compares the food-production efficiencies of integrated rice-fish farming and rice monoculture and evaluates how these farming systems contribute to sustainable food production in the Mekong Delta. The study explores how food-production efficiencies are influenced by the systems’ ecological connectivity by comparing more integrated systems that apply integrated rice-fish farming and integrated pest management (IPM) with less integrated systems farming only rice. Rice-fish farmers with plenty of fish had significantly higher rice yields than farmers with less or no fish, especially during the second crop when the rice was grown together with the fish. A positive correlation between the fish and rice yields, indicated synergistic effects between the fish and rice, due to strengthened ecological connectivity and trophic interactions within the rice-field ecosystem. Overall, rice-fish farmers had higher rice yields than rice farmers, despite using lower amounts of fertilizers and pesticides. They also had lower rice production costs compared to rice farmers, partly because the fish helped fertilize the rice and control rice pests. They had a significantly higher profit and benefit cost ratio than rice farmers because of lower production costs, and high rice and fish yields. The results indicate that food-production efficiencies in the Mekong Delta can be enhanced through diversification and increased ecological connectivity, leading to a more efficient use of rice field ecosystem services that support a long-term and healthy production of food.